Pengembangan Bahan Ajar Materi Garis Istimewa pada Segitiga dengan Pendekatan Problem Posing berbantuan Geogebra - Elis Nurhayati; Winda Nengsih; Euis Eti Rohaeti; Indri Herdiman (Didaktik Matematika, 2018)
This study is a developmental research aiming to produce Geogebra-assisted teaching and learning materials through Problem Posing for topic of Line Special in Triangle at year 7. This study uses Thiagarajans model of developmental research, without disseminate stage. The learning materials developed in this study were lesson plans and student worksheets. The subjects of this study were grade seven students at a private school in Cianjur Regency. In total, 13 male and 15 female students participated in this study. The results of this study show that (1) based validators review, the research instruments developed in this were very valid and practical, (2) based on students response, teaching materials fulfilled the practical category, and (3) based on the implementation in the classroom, student worksheets satisfied the effective category.